Pemetaan dan Analisis Pengelolaan Sampah di Kawasan Ekonomi Khusus (KEK) Mandalika, NTB: Mapping and Waste Management Analysis in The Special Economic Zone (SEZ) Mandalika, NTB - lestari, andi tri; Anwar, Hairil; Syaputra, Maiser (Forestry Faculty of Hasanuddin University, 2024)
One of the main tourist destinations in NTB Province currently is the Mandalika area, part of the Central Lombok region. This area is designated a Special Economic Zone (SEZ) based on PP Number 52 of 2014. Tourist visits increased drastically at the 2021 World Superbike (WSBK) event, and it is assumed that this will grow at the upcoming 2022 MotoGP event. An increase in the number of tourists has a positive and negative impact on the environment, along with increasing waste production. This research analyzed waste generation, composition, and effective waste management in the Mandalika SEZ. Analysis of waste production and composition will be carried out by referring to SNI 19-3964-1994 regarding methods for collecting and measuring samples of urban waste production and composition while analyzing waste management in the Mandalika SEZ, which was carried out by interview. The research results show that the average waste production in the Mandalika SEZ is 58.16 kg/Day. The most dominant waste composition is organic waste originating from food scraps, with an average of 39.56 kg/day, followed by the amount of plastic waste with an average of 16.41 kg/day. The smallest amount of waste at the research location is paper waste, with an average of 0.48 kg/day, and other waste is used diapers, with an average of 1.71 kg/day. The Waste Management Model shows that the average waste produced at the research location is 58.16 kg in one day. As a result of the indicators of waste production, in just one month, the waste production reached 1744.80 kg/day if it was not handled at all. Based on the research results, waste management modeling was produced by increasing public awareness, organic waste management using the Anaerobic Digestion Method and inorganic waste management using the recycling method. This modeling shows that the method applied can reduce waste production by up to 0.15%, namely 263.10 kg/day.